Electricity, relativity and magnetism a unified text - Craik, Derek J. (John Wiley, 1999)
Electricity, Relativity and Magnetism: A Unified Text presents the first complete and systematic derivation of the principles of magnetism and electromagnetism from Coulomb s law and the theory of special relativity alone. Most books on magnetism introduce the subject in terms of experimental observations, as if magnetism were distinct from, albeit associated with, electricity. The topic of relativity is often mentioned, but almost as an afterthought, rather than as a crucial element of the argument. In this new book from Dr Derek Craik, the important links between electricity and magnetism, via special relativity, are emphasized, leading the reader to a more meaningful and profound understanding of the subject.